Tower down - Hagberg, David (Hagberg, David. Kirk McGarvey adventures, 2017)
A freelance killer, code-named Al-Nassar, the Eagle, causes a pencil tower in Manhattan to fall. CIA agent Kirk Harvey suspects the Saudi Arabian government is behind it despite their status as US allies.